AB0301 Vascular Markers in Woman and in Men with Rheumatoid Arthritis. (10th June 2014) - Lo Gullo, A.; Mandraffino, G.; Sardo, M.A.; Imbalzano, E.; Mamone, F.; Lo Gullo, R.; Bagnato, G.; Saitta, A.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased morbidity and mortality rates due to cardiovascular disease, and this occurs early in the disease process. In RA an impairment of the number and the activity of circulating progenitor cells, including CD34+ cells and endothelial progenitor cells, is involved in the development of endothelial damage and cardiovascular diseases (CVD). Objectives: To evaluate CD34+ cell number and vascular markers in woman and men with RA. Methods: We enrolled 48 patients (mean age 50.6±7.6), 22 men (mean age 51.1±7.9) and 26 women (mean age 50.2±7.4); patients were enrolled at the time of diagnosis, if they did not present with cardiovascular risk factors. CD34+, C-reactive protein (CRP), fibrinogen, carotid intima-media thickness (cIMT), Pulse wave velocity (PWV), were assessed at baseline. We investigated the relationships among cell number, inflammatory markers, and vascular parameters in woman and men. Results: No differences in CD34+ cell number (1.79±1.34 vs 1.99±1.59), fibrinogen (361.9±64.2 vs 343.1±74.0), CRP (3.32±1.0 vs 3.12±0.96), PWV (7.77±2.3 vs 7.34±2.9), and cIMT (1.11±0.3 vs 1.14±0.1) between woman and men. In both groups was confirmed a correlation between CD34+ and Fibrinogen, CRP, PWV (all p<0.01). Conclusions: Despite RA affects more woman than men, we found no differences in vascular parameters between men and woman at the onset of the disease. References: Kuller LH et al. Determinants of mortality among postmenopausal woman who report rheumatoid arthritis in the Woman's Health Initiative. Arthritis and Rheumatism 2013. (Epub ahead of Print). Lo Gullo A et al. Circulating progenitor cells in rheumatoid arthritis: association with inflammation and oxidative stress. Scand J Rheumatol 2013 (Epub ahead of Print). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5976